Designing spaces for early childhood development : sparking learning & creativity - Kotnik, Jure (Mulgrave, Victoria : The Images Publishing Group Pty Ltd, 2017)
Contemporary pedagogy suggests children's growth and development takes place through experiences. The task of the kindergarten designer and educator is to provide authentic, stimulating and meaningful environments, full of rich and active hands-on experiences that will facilitate each child's access to the natural or human worlds, until they have assimilated everything they need to thrive and grow. This book is intended to uncover the relationship between early childhood space design and childhood development through an exciting selection of kindergarten, childcare, and nursery (crèche) designs from around the world. As a standout, the work focuses on the details of indoor spaces and outdoor playgrounds. Each case includes highlighted commentary by the designer, explaining how their work helps children to shape their own personal curriculum. Case studies include interviews with architects that present valuable insights. Highly illustrated in full-color throughout, this book hopes to spark the design inspirations of kindergarten architects and interior designers, as well as outdoor playground designers, on how to design children's education and care centers. --Amazon
Keywords: Kindergarten facilities -- Designs and plans; Early childhood education; Architecture